Various siliceous micro-fossil and calcacerous nannofossil records from the Equatorial Atlantic (last 25 ka) - Isabelle M Gil; Jerry F McManus; Andreia Rebotim; Aurea Narciso; Emilia Salgueiro; Fatima F Abrantes (PANGAEA, 2023)
Relatively high opal concentrations are measured in equatorial Atlantic sediments from the most recent deglaciation. To shed light on their causes, seven cores were analyzed for their content of siliceous (diatom, silicoflagellates, radiolarians, phytoliths and sponge spicules) and calcareous (coccolithophores) microfossils. An early deglacial signal is detected at the time of rising boreal summer insolation ca. 18 ka by the coccolithophores. The surface freshening is likely due to the rain belt associated with the intertropical convergence zone - ITCZ, implying its southward shift relatively to its present-day average positioning. The diatom assemblages corresponding to the following increase in diatom abundances ca. 15.5 ka suggest the formation of a cold tongue of upwelled water associated with tropical instability waves propagating westward. Such conditions occur at present during boreal summer, when southerly trade winds are intensified, and the ITCZ shifts northward. The presence of the diatom Ethmodiscus rex (Wallich) Hendey and the coccolithophore Florisphera profunda indicates a deep thermocline and nutrient enrichment of the lower photic zone, revealing that Si-rich southern sourced water (SSW) likely contributed to enhanced primary productivity during this time interval. The discrepancies between the maximum opal concentrations and siliceous marine microfossils records evidence the contribution of freshwater diatoms and phytoliths, indicative of other processes. The definition of the nature of the opal record suggests successive productivity conditions associated with specific atmospheric settings determining the latitudinal ITCZ positioning and the development of oceanic processes; and major oceanic circulation changes permitting the contribution of SSW to marine productivity at this latitude.